A Review of Instruments that Measure LGBTQ Affirmation and Discrimination Constructs in Adults. Issue Volume 11:Issues 4(2017) (2nd October 2017) - Peterson, Christina Hamme; Dalley, Lauren M.; Dombrowski, Stefan C.; Maier, Collin
ABSTRACT: In this article, the authors review measures of adult lesbian, gay, bisexual, transgender, queer (LGBTQ) affirmation and discrimination constructs in five categories: counselor competency, attitudes toward LGBTQ, experiences of discrimination, internalized attitudes, and sexual identity. Within each category the authors list scales, scale descriptions, validity, reliability, and normative data. Their aim was not to conduct a systematic review, but rather to provide readers with a sampling of available tools. The authors selected measures for inclusion on the basis of usage (assessed via average annual citation rates) or uniqueness of the construct or population addressed. Finally, the authors conclude with recommendations for future development of measures.